Perspectives on multisectoral accountability framework to end tuberculosis in the Eastern Europe and Central Asia region: a mixed-methods study - Chorna, Yuliya; Lukash, Ievgeniia-Galyna; Kalancha, Yuliia; Tonkonoh, Lesia; Abdullaeva, Marifat; Adenov, Malik; Chuprynska, Mariia; Hasanova, Sayohat; Ibragimova, Oxana; Jazybekova, Panagul; Kamenska, Nataliia; Klymenko, Olya; et al. (BMC global and public health, 2025)
Background Sectors beyond health are essential to combatting a social disease such as tuberculosis (TB). The engagement of the community and civil society sector in Eastern Europe and Central Asia was assessed as part of a broader baseline assessment of multisectoral engagement in national TB responses. Methods This was a mixed-methods community-based study. Surveys, interviews, and focus groups were conducted online with TB-engaged community and civil society representatives in Belarus, Kazakhstan, Moldova, Tajikistan, and Ukraine from January to June 2021. Quantitative data, analyzed using descriptive statistics, were triangulated with thematic qualitative analysis. A multisectoral accountability framework and community, rights, and gender framework for TB were used to triangulate the findings and inform data interpretations. Results Participants ( n = 160) included leads, service providers from 74 organizations, and TB survivors. Of 53 survey respondents, most ( n = 41, 77·4%) indicated strong/complete agreement to participating in TB service delivery and gender, stigma, and/or legal assessments ( n = 27, 50·9%) and research processes ( n = 30, 56·6%). However, few indicated inclusion in operational planning and budgeting ( n = 13, 24·5%), or political and program impact of community-led monitoring ( n = 16, 30·2%), and almost none ( n = 2, 3.8%) confirmed dedicated budgets for their TB-related work. Inquiry into the dimensions and criteria for multisectoral actions and accountability revealed their key, yet limited, role in attending to social determinants, with wider engagement hindered by precarious funding. Several organizations balanced building partnerships with other sectors engaged in the TB response against advocacy activities. Inherent obligations toward TB-affected communities were at times overshadowed by obligations to donors and state actors. Coordinating bodies for donor funds, which were multisectoral by design, presented an opportunity to bolster accountability actions within the TB response. Conclusions Multisectoral engagement and accountability for TB are a laudable and necessary goal to end TB. Sustainable mechanisms to support the meaningful involvement of TB-affected communities and civil society are needed, particularly in the context of donor transitions.